2018
DOI: 10.1111/bph.14538
|View full text |Cite
|
Sign up to set email alerts
|

Sirtuin 1 represses PKC‐ζ activity through regulating interplay of acetylation and phosphorylation in cardiac hypertrophy

Abstract: Background and Purpose Activation of PKC‐ζ is closely linked to the pathogenesis of cardiac hypertrophy. PKC‐ζ can be activated by certain lipid metabolites such as phosphatidylinositol (3,4,5)‐trisphosphate and ceramide. However, its endogenous negative regulators are not well defined. Here, the role of the sirtuin1‐PKC‐ζ signalling axis and the underlying molecular mechanisms were investigated in cardiac hypertrophy. Experimental Approach Cellular hypertrophy in cultures of cardiac myocytes, from neonatal Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 56 publications
0
21
0
Order By: Relevance
“…While the biological functions of PKC phosphorylation have long been characterized, it recently emerged that at least one PKC isozyme, PKCζ, may also undergo posttranslational modification by lysine-acetylation [54]. The authors of this study found that the deacetylase SIRT1 represses PKCζ activation by inhibiting its initial PDK1 mediated phosphorylation.…”
Section: Receptors For Activated C-kinase (Racks) and Other Proteins mentioning
confidence: 82%
“…While the biological functions of PKC phosphorylation have long been characterized, it recently emerged that at least one PKC isozyme, PKCζ, may also undergo posttranslational modification by lysine-acetylation [54]. The authors of this study found that the deacetylase SIRT1 represses PKCζ activation by inhibiting its initial PDK1 mediated phosphorylation.…”
Section: Receptors For Activated C-kinase (Racks) and Other Proteins mentioning
confidence: 82%
“…Acetylation and trimethylation on H3K27 play opposing roles at the promoter regions of genes involved in cardiac hypertrophy . A previous study has shown that SIRT1 attenuated the PKC‐ζ activity via mediating the interplay of acetylation and phosphorylation in cardiac hypertrophy (Figure ). In conclusion, these findings suggest that crosstalk between different pairs of PTMs is essential for cardiac function.…”
Section: The Multifaceted Control Of Ptmmentioning
confidence: 95%
“…In addition, cardiomyocyte hypertrophy was attenuated by transcription factor 3 (ATF3), binding with the Map2K3 promoter, resulting in recruiting HDAC1 and suppressing MAP2K3‐p38 Signalling . Furthermore, the class III HDAC, sirtuin 1 (SITR1), reportedly prevented cardiomyocyte hypertrophy by negatively regulating the acetylation and phosphorylation levels of protein kinase C‐ζ (Table ) . Likewise, Class I HDACs attenuated cardiac hypertrophy by repressing the TSC2‐dependent mammalian target of rapamycin pathway .…”
Section: Acetylation and Methylationmentioning
confidence: 99%
“…1a and b). Similarly, the mRNA and protein levels of SNX3 were clearly induced in the myocardium of mouse HF model by subcutaneous (s.c.) injection of ISO (3 mg/kg/day, a classic hypertrophic agonist [30][31][32] ) for four weeks (Supplementary Figure S1b-d). These results suggest that SNX3 was associated with cardiac hypertrophy and HF in human and mice.…”
Section: Snx3 Expression Was Up-regulated In Human and Mouse Failing mentioning
confidence: 99%
“…Experimental animals were housed, bred, and maintained in the speci c pathogen-free (SPF) facility of the Experimental Animal Center of Sun Yat-sen University. As we previously described 30 , the transthoracic 2D-guided M-mode echocardiography (such as heart function and global cardiac volumes) was assessed using by a Technos MPX ultrasound system (ESAOTE, SpAESAOTE SpA, Italy) equipped with an 40-MHz scan probe. The Vevo 2100 imaging software was used for measurements and calculations.…”
Section: Animal Studiesmentioning
confidence: 99%